2012
DOI: 10.2323/jgam.58.145
|View full text |Cite
|
Sign up to set email alerts
|

<i>Wickerhamomyces tratensis</i> sp. nov. and <i>Candida namnaoensis</i> sp. nov., two novel ascomycetous yeast species in the <i>Wickerhamomyces</i> clade found in Thailand

Abstract: IntroductionDuring the course of a study of yeasts living in the natural environment of Thailand, two strains of yeasts were isolated from a fl ower of Sonneratia caseolaris L. and insect frass of a tree collected from different places in Thailand. The two strains are closely related in the D1/D2 domain sequences of the large subunit (LSU) rRNA gene and are located in the Wickerhamomyces clade. The DNA-DNA hybridization experiment suggested that the two strains are closely related but different species. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Some characteristics of the genus Wickerhamomyces are the formation of hat-shaped ascospores or spherical ascospores with an equatorial ledge; cell division is by multilateral budding; some species form pseudohyphae and true hyphae; asci are globose to ellipsoid, and unconjugated; some species ferment glucose and they do not assimilate methanol or hexadecane; and the diazonium blue B reaction is negative (Kurtzman et al, , 2011a. Species currently accepted in the genus have been isolated from soil (Limtong et al, 2009;Kurtzman et al, 2011a;Shin et al, 2011;Limtong et al, 2012), plant material (Groenewald et al, 2011;Kaewwichian et al, 2013;James et al, 2014), tree exudates (Kurtzman et al, 2011a;de García et al, 2010), flowers (Nakase et al, 2012;James et al, 2014), digestive tract of insects (Hui et al, 2013;James et al, 2014), insect frass (Kurtzman et al, 2011a), larvae of diptera (Rosa et al, 2009), birds (Francesca et al, 2013), natural fermentation of coffee cherries (Silva et al, 2000) and brined vegetables (Etchells & Bell, 1950). Acromyrmex lundii is an ant species in the tribe Attini (Hymenoptera: Formicidae), which have a mutualistic relationship with basidiomycetous fungi in the order Agaricales (Bonetto, 1959).…”
mentioning
confidence: 99%
“…Some characteristics of the genus Wickerhamomyces are the formation of hat-shaped ascospores or spherical ascospores with an equatorial ledge; cell division is by multilateral budding; some species form pseudohyphae and true hyphae; asci are globose to ellipsoid, and unconjugated; some species ferment glucose and they do not assimilate methanol or hexadecane; and the diazonium blue B reaction is negative (Kurtzman et al, , 2011a. Species currently accepted in the genus have been isolated from soil (Limtong et al, 2009;Kurtzman et al, 2011a;Shin et al, 2011;Limtong et al, 2012), plant material (Groenewald et al, 2011;Kaewwichian et al, 2013;James et al, 2014), tree exudates (Kurtzman et al, 2011a;de García et al, 2010), flowers (Nakase et al, 2012;James et al, 2014), digestive tract of insects (Hui et al, 2013;James et al, 2014), insect frass (Kurtzman et al, 2011a), larvae of diptera (Rosa et al, 2009), birds (Francesca et al, 2013), natural fermentation of coffee cherries (Silva et al, 2000) and brined vegetables (Etchells & Bell, 1950). Acromyrmex lundii is an ant species in the tribe Attini (Hymenoptera: Formicidae), which have a mutualistic relationship with basidiomycetous fungi in the order Agaricales (Bonetto, 1959).…”
mentioning
confidence: 99%
“…The genus Wickerhamomyces was proposed to accommodate 17 species that were transferred from the genera Pichia , Williopsis and Hansenula as a result of phylogenetic analysis of nucleotide divergence in the genes coding for the large-subunit (LSU) and small-subunit rRNAs and for elongation factor 1α (Kurtzman et al , 2008; Kurtzman, 2011). The number of Wickerhamomyces species was subsequently increased by the discovery of Wickerhamomyces edaphicus (Limtong et al , 2009), W. queroliae (Rosa et al , 2009), W. patagonicus (de García et al , 2010), W. chaumierensis (Groenewald et al , 2011), W. ochangensis (Shin et al , 2011), W. tratensis (Nakase et al , 2012) and W. xylosica (Limtong et al , 2012).…”
mentioning
confidence: 99%
“…Ten strains were identical and were located in the genus Wickerhamomyces () in the phylogenetic tree based on the D1/D2 domain sequences of the LSU rRNA gene. At the time of writing, the genus Wickerhamomyces has 24 known species including seven recently described species: Wickerhamomyces edaphicus , Wickerhamomyces queroliae , Wickerhamomyces patagonicus , Wickerhamomyces chaumierensis , Wickerhamomyces ochangensis , Wickerhamomyces xylosica and Wickerhamomyces tratensis (de García et al , 2010; Groenewald et al , 2011; Kurtzman, 2011a; Limtong et al , 2009, 2012; Nakase et al , 2012; Rosa et al , 2009; Shin et al , 2011). The ten novel strains had identical sequences and were closely related to Wickerhamomyces hampshirensis , but they differed from this species by 14 nt substitutions and 1 gap (2.6 %) in the D1/D2 domain sequences of the LSU rRNA gene and by 24 nt substitutions and 14 gaps (6.4 %) in the ITS regions including 5.8S rRNA gene.…”
mentioning
confidence: 99%
“…The two genera Wickerhamomyces and Cyberlindnera were located in different clades in the family Wickerhamomycetaceae based on multigene sequence analysis (Kurtzman et al , 2008). Many species of both genera have been isolated from valuable substrates associated with insects (de García et al , 2010; Mestre et al , 2011; Nakase et al , 2012; Rosa et al , 2009). In particular, Suh & Zhou (2010) reported that two strains of W. hampshirensis were isolated from ambrosia beetle galleries of Xyloterinus politus .…”
mentioning
confidence: 99%